Aspek Psikologi Hukum, Alqur’an dan Hadis Terhadap Tindak Pidana Perjudian Online (Aspects of Legal Psychology, The Quran and Hadith on Online Gambling Crimes) - Ardi Muthahir, SH, MH; Raesitha Zildjianda; Yolanda Fiorence Lingga (CV Rewang Rencang, 2024)
ABSTRACT The reality (das sein) is that there are still many people who try to break the law. One of the crimes resulting from internet misuse is online gambling. The increasingly rapid use of the internet, gambling is shifting to online gambling which is more practical and safe. Online gambling is a form of social deviance and there is a need for the role of legal psychology in preventing criminal acts of online gambling. Islam prohibits online gambling because it has bad impacts, one of which is preventing perpetrators from carrying out prayers and other forms of worship. Keywords: Legal psychology, Al-Qur'an, Hadith, Online Gambling.